The mixtape - Cherry, Brittainy C. (Montlake, 2021)
Emery has never felt more alone. Raising her daughter is both her pleasure and her pain as she struggles to hold on to her job as a bartender and keep a roof over their heads. With no one to help them--no support system--any unexpected expense or late bill could turn their whole world upside down. Reeling from the death of his twin brother and bandmate, rock star Oliver Smith is trying to drink his problems away. Apparently he isn't very good at it; they follow him wherever he goes. Also in hot pursuit are the paparazzi, who catch Oliver at his lowest low. He could have walked into any bar in California, but he walked into hers. Emery helps Oliver lose the crowd, and they find themselves alone: two people whose paths are marked with loss and pain. However, they hold an unshakable hope for healing. They find solace together, but can their love withstand the world?